MAYBE Initial complexity problem: 1: T: (?, 1) f26(a, b) -> f2(a, b) (?, 1) f2(a, b) -> f2(a, b) (?, 1) f9(a, b) -> f12(a, c) [ 5 >= a /\ 0 >= c + 1 ] (?, 1) f9(a, b) -> f12(a, c) [ 5 >= a /\ c >= 1 ] (?, 1) f12(a, b) -> f9(a + 1, b) [ a >= 6 ] (?, 1) f28(a, b) -> f30(a, b) (?, 1) f20(a, b) -> f20(a - 1, b) [ a >= 3 ] (?, 1) f20(a, b) -> f9(a, b) [ 2 >= a ] (?, 1) f12(a, b) -> f9(a + 1, b) [ 5 >= a ] (?, 1) f9(a, b) -> f20(a, 0) [ 5 >= a ] (?, 1) f9(a, b) -> f20(a, b) [ a >= 6 ] (1, 1) f0(a, b) -> f9(c, b) start location: f0 leaf cost: 0 Repeatedly removing leaves of the complexity graph in problem 1 produces the following problem: 2: T: (?, 1) f26(a, b) -> f2(a, b) (?, 1) f2(a, b) -> f2(a, b) (?, 1) f9(a, b) -> f12(a, c) [ 5 >= a /\ 0 >= c + 1 ] (?, 1) f9(a, b) -> f12(a, c) [ 5 >= a /\ c >= 1 ] (?, 1) f12(a, b) -> f9(a + 1, b) [ a >= 6 ] (?, 1) f20(a, b) -> f20(a - 1, b) [ a >= 3 ] (?, 1) f20(a, b) -> f9(a, b) [ 2 >= a ] (?, 1) f12(a, b) -> f9(a + 1, b) [ 5 >= a ] (?, 1) f9(a, b) -> f20(a, 0) [ 5 >= a ] (?, 1) f9(a, b) -> f20(a, b) [ a >= 6 ] (1, 1) f0(a, b) -> f9(c, b) start location: f0 leaf cost: 1 Testing for reachability in the complexity graph removes the following transitions from problem 2: f26(a, b) -> f2(a, b) f2(a, b) -> f2(a, b) f12(a, b) -> f9(a + 1, b) [ a >= 6 ] We thus obtain the following problem: 3: T: (?, 1) f20(a, b) -> f9(a, b) [ 2 >= a ] (?, 1) f20(a, b) -> f20(a - 1, b) [ a >= 3 ] (?, 1) f12(a, b) -> f9(a + 1, b) [ 5 >= a ] (?, 1) f9(a, b) -> f20(a, b) [ a >= 6 ] (?, 1) f9(a, b) -> f20(a, 0) [ 5 >= a ] (?, 1) f9(a, b) -> f12(a, c) [ 5 >= a /\ c >= 1 ] (?, 1) f9(a, b) -> f12(a, c) [ 5 >= a /\ 0 >= c + 1 ] (1, 1) f0(a, b) -> f9(c, b) start location: f0 leaf cost: 1 Applied AI with 'oct' on problem 3 to obtain the following invariants: For symbol f12: -X_1 + 5 >= 0 This yielded the following problem: 4: T: (1, 1) f0(a, b) -> f9(c, b) (?, 1) f9(a, b) -> f12(a, c) [ 5 >= a /\ 0 >= c + 1 ] (?, 1) f9(a, b) -> f12(a, c) [ 5 >= a /\ c >= 1 ] (?, 1) f9(a, b) -> f20(a, 0) [ 5 >= a ] (?, 1) f9(a, b) -> f20(a, b) [ a >= 6 ] (?, 1) f12(a, b) -> f9(a + 1, b) [ -a + 5 >= 0 /\ 5 >= a ] (?, 1) f20(a, b) -> f20(a - 1, b) [ a >= 3 ] (?, 1) f20(a, b) -> f9(a, b) [ 2 >= a ] start location: f0 leaf cost: 1 By chaining the transition f9(a, b) -> f12(a, c) [ 5 >= a /\ 0 >= c + 1 ] with all transitions in problem 4, the following new transition is obtained: f9(a, b) -> f9(a + 1, c) [ 5 >= a /\ 0 >= c + 1 /\ -a + 5 >= 0 ] We thus obtain the following problem: 5: T: (?, 2) f9(a, b) -> f9(a + 1, c) [ 5 >= a /\ 0 >= c + 1 /\ -a + 5 >= 0 ] (1, 1) f0(a, b) -> f9(c, b) (?, 1) f9(a, b) -> f12(a, c) [ 5 >= a /\ c >= 1 ] (?, 1) f9(a, b) -> f20(a, 0) [ 5 >= a ] (?, 1) f9(a, b) -> f20(a, b) [ a >= 6 ] (?, 1) f12(a, b) -> f9(a + 1, b) [ -a + 5 >= 0 /\ 5 >= a ] (?, 1) f20(a, b) -> f20(a - 1, b) [ a >= 3 ] (?, 1) f20(a, b) -> f9(a, b) [ 2 >= a ] start location: f0 leaf cost: 1 By chaining the transition f9(a, b) -> f12(a, c) [ 5 >= a /\ c >= 1 ] with all transitions in problem 5, the following new transition is obtained: f9(a, b) -> f9(a + 1, c) [ 5 >= a /\ c >= 1 /\ -a + 5 >= 0 ] We thus obtain the following problem: 6: T: (?, 2) f9(a, b) -> f9(a + 1, c) [ 5 >= a /\ c >= 1 /\ -a + 5 >= 0 ] (?, 2) f9(a, b) -> f9(a + 1, c) [ 5 >= a /\ 0 >= c + 1 /\ -a + 5 >= 0 ] (1, 1) f0(a, b) -> f9(c, b) (?, 1) f9(a, b) -> f20(a, 0) [ 5 >= a ] (?, 1) f9(a, b) -> f20(a, b) [ a >= 6 ] (?, 1) f12(a, b) -> f9(a + 1, b) [ -a + 5 >= 0 /\ 5 >= a ] (?, 1) f20(a, b) -> f20(a - 1, b) [ a >= 3 ] (?, 1) f20(a, b) -> f9(a, b) [ 2 >= a ] start location: f0 leaf cost: 1 Testing for reachability in the complexity graph removes the following transition from problem 6: f12(a, b) -> f9(a + 1, b) [ -a + 5 >= 0 /\ 5 >= a ] We thus obtain the following problem: 7: T: (?, 1) f20(a, b) -> f9(a, b) [ 2 >= a ] (?, 1) f20(a, b) -> f20(a - 1, b) [ a >= 3 ] (?, 2) f9(a, b) -> f9(a + 1, c) [ 5 >= a /\ c >= 1 /\ -a + 5 >= 0 ] (?, 2) f9(a, b) -> f9(a + 1, c) [ 5 >= a /\ 0 >= c + 1 /\ -a + 5 >= 0 ] (?, 1) f9(a, b) -> f20(a, b) [ a >= 6 ] (?, 1) f9(a, b) -> f20(a, 0) [ 5 >= a ] (1, 1) f0(a, b) -> f9(c, b) start location: f0 leaf cost: 1 By chaining the transition f9(a, b) -> f20(a, b) [ a >= 6 ] with all transitions in problem 7, the following new transition is obtained: f9(a, b) -> f20(a - 1, b) [ a >= 6 /\ a >= 3 ] We thus obtain the following problem: 8: T: (?, 2) f9(a, b) -> f20(a - 1, b) [ a >= 6 /\ a >= 3 ] (?, 1) f20(a, b) -> f9(a, b) [ 2 >= a ] (?, 1) f20(a, b) -> f20(a - 1, b) [ a >= 3 ] (?, 2) f9(a, b) -> f9(a + 1, c) [ 5 >= a /\ c >= 1 /\ -a + 5 >= 0 ] (?, 2) f9(a, b) -> f9(a + 1, c) [ 5 >= a /\ 0 >= c + 1 /\ -a + 5 >= 0 ] (?, 1) f9(a, b) -> f20(a, 0) [ 5 >= a ] (1, 1) f0(a, b) -> f9(c, b) start location: f0 leaf cost: 1 By chaining the transition f9(a, b) -> f20(a - 1, b) [ a >= 6 /\ a >= 3 ] with all transitions in problem 8, the following new transition is obtained: f9(a, b) -> f20(a - 2, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 ] We thus obtain the following problem: 9: T: (?, 3) f9(a, b) -> f20(a - 2, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 ] (?, 1) f20(a, b) -> f9(a, b) [ 2 >= a ] (?, 1) f20(a, b) -> f20(a - 1, b) [ a >= 3 ] (?, 2) f9(a, b) -> f9(a + 1, c) [ 5 >= a /\ c >= 1 /\ -a + 5 >= 0 ] (?, 2) f9(a, b) -> f9(a + 1, c) [ 5 >= a /\ 0 >= c + 1 /\ -a + 5 >= 0 ] (?, 1) f9(a, b) -> f20(a, 0) [ 5 >= a ] (1, 1) f0(a, b) -> f9(c, b) start location: f0 leaf cost: 1 By chaining the transition f9(a, b) -> f20(a - 2, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 ] with all transitions in problem 9, the following new transition is obtained: f9(a, b) -> f20(a - 3, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 ] We thus obtain the following problem: 10: T: (?, 4) f9(a, b) -> f20(a - 3, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 ] (?, 1) f20(a, b) -> f9(a, b) [ 2 >= a ] (?, 1) f20(a, b) -> f20(a - 1, b) [ a >= 3 ] (?, 2) f9(a, b) -> f9(a + 1, c) [ 5 >= a /\ c >= 1 /\ -a + 5 >= 0 ] (?, 2) f9(a, b) -> f9(a + 1, c) [ 5 >= a /\ 0 >= c + 1 /\ -a + 5 >= 0 ] (?, 1) f9(a, b) -> f20(a, 0) [ 5 >= a ] (1, 1) f0(a, b) -> f9(c, b) start location: f0 leaf cost: 1 By chaining the transition f9(a, b) -> f20(a - 3, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 ] with all transitions in problem 10, the following new transition is obtained: f9(a, b) -> f20(a - 4, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 ] We thus obtain the following problem: 11: T: (?, 5) f9(a, b) -> f20(a - 4, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 ] (?, 1) f20(a, b) -> f9(a, b) [ 2 >= a ] (?, 1) f20(a, b) -> f20(a - 1, b) [ a >= 3 ] (?, 2) f9(a, b) -> f9(a + 1, c) [ 5 >= a /\ c >= 1 /\ -a + 5 >= 0 ] (?, 2) f9(a, b) -> f9(a + 1, c) [ 5 >= a /\ 0 >= c + 1 /\ -a + 5 >= 0 ] (?, 1) f9(a, b) -> f20(a, 0) [ 5 >= a ] (1, 1) f0(a, b) -> f9(c, b) start location: f0 leaf cost: 1 By chaining the transition f9(a, b) -> f20(a - 4, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 ] with all transitions in problem 11, the following new transitions are obtained: f9(a, b) -> f9(a - 4, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ 2 >= a - 4 ] f9(a, b) -> f20(a - 5, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 ] We thus obtain the following problem: 12: T: (?, 6) f9(a, b) -> f9(a - 4, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ 2 >= a - 4 ] (?, 6) f9(a, b) -> f20(a - 5, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 ] (?, 1) f20(a, b) -> f9(a, b) [ 2 >= a ] (?, 1) f20(a, b) -> f20(a - 1, b) [ a >= 3 ] (?, 2) f9(a, b) -> f9(a + 1, c) [ 5 >= a /\ c >= 1 /\ -a + 5 >= 0 ] (?, 2) f9(a, b) -> f9(a + 1, c) [ 5 >= a /\ 0 >= c + 1 /\ -a + 5 >= 0 ] (?, 1) f9(a, b) -> f20(a, 0) [ 5 >= a ] (1, 1) f0(a, b) -> f9(c, b) start location: f0 leaf cost: 1 Repeatedly propagating knowledge in problem 12 produces the following problem: 13: T: (?, 6) f9(a, b) -> f9(a - 4, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ 2 >= a - 4 ] (1, 6) f9(a, b) -> f20(a - 5, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 ] (?, 1) f20(a, b) -> f9(a, b) [ 2 >= a ] (?, 1) f20(a, b) -> f20(a - 1, b) [ a >= 3 ] (?, 2) f9(a, b) -> f9(a + 1, c) [ 5 >= a /\ c >= 1 /\ -a + 5 >= 0 ] (?, 2) f9(a, b) -> f9(a + 1, c) [ 5 >= a /\ 0 >= c + 1 /\ -a + 5 >= 0 ] (?, 1) f9(a, b) -> f20(a, 0) [ 5 >= a ] (1, 1) f0(a, b) -> f9(c, b) start location: f0 leaf cost: 1 By chaining the transition f9(a, b) -> f20(a - 5, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 ] with all transitions in problem 13, the following new transitions are obtained: f9(a, b) -> f9(a - 5, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ 2 >= a - 5 ] f9(a, b) -> f20(a - 6, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 ] We thus obtain the following problem: 14: T: (1, 7) f9(a, b) -> f9(a - 5, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ 2 >= a - 5 ] (1, 7) f9(a, b) -> f20(a - 6, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 ] (?, 6) f9(a, b) -> f9(a - 4, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ 2 >= a - 4 ] (?, 1) f20(a, b) -> f9(a, b) [ 2 >= a ] (?, 1) f20(a, b) -> f20(a - 1, b) [ a >= 3 ] (?, 2) f9(a, b) -> f9(a + 1, c) [ 5 >= a /\ c >= 1 /\ -a + 5 >= 0 ] (?, 2) f9(a, b) -> f9(a + 1, c) [ 5 >= a /\ 0 >= c + 1 /\ -a + 5 >= 0 ] (?, 1) f9(a, b) -> f20(a, 0) [ 5 >= a ] (1, 1) f0(a, b) -> f9(c, b) start location: f0 leaf cost: 1 By chaining the transition f9(a, b) -> f20(a - 6, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 ] with all transitions in problem 14, the following new transitions are obtained: f9(a, b) -> f9(a - 6, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ 2 >= a - 6 ] f9(a, b) -> f20(a - 7, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 ] We thus obtain the following problem: 15: T: (1, 8) f9(a, b) -> f9(a - 6, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ 2 >= a - 6 ] (1, 8) f9(a, b) -> f20(a - 7, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 ] (1, 7) f9(a, b) -> f9(a - 5, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ 2 >= a - 5 ] (?, 6) f9(a, b) -> f9(a - 4, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ 2 >= a - 4 ] (?, 1) f20(a, b) -> f9(a, b) [ 2 >= a ] (?, 1) f20(a, b) -> f20(a - 1, b) [ a >= 3 ] (?, 2) f9(a, b) -> f9(a + 1, c) [ 5 >= a /\ c >= 1 /\ -a + 5 >= 0 ] (?, 2) f9(a, b) -> f9(a + 1, c) [ 5 >= a /\ 0 >= c + 1 /\ -a + 5 >= 0 ] (?, 1) f9(a, b) -> f20(a, 0) [ 5 >= a ] (1, 1) f0(a, b) -> f9(c, b) start location: f0 leaf cost: 1 By chaining the transition f9(a, b) -> f20(a - 7, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 ] with all transitions in problem 15, the following new transitions are obtained: f9(a, b) -> f9(a - 7, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ 2 >= a - 7 ] f9(a, b) -> f20(a - 8, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ a - 7 >= 3 ] We thus obtain the following problem: 16: T: (1, 9) f9(a, b) -> f9(a - 7, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ 2 >= a - 7 ] (1, 9) f9(a, b) -> f20(a - 8, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ a - 7 >= 3 ] (1, 8) f9(a, b) -> f9(a - 6, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ 2 >= a - 6 ] (1, 7) f9(a, b) -> f9(a - 5, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ 2 >= a - 5 ] (?, 6) f9(a, b) -> f9(a - 4, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ 2 >= a - 4 ] (?, 1) f20(a, b) -> f9(a, b) [ 2 >= a ] (?, 1) f20(a, b) -> f20(a - 1, b) [ a >= 3 ] (?, 2) f9(a, b) -> f9(a + 1, c) [ 5 >= a /\ c >= 1 /\ -a + 5 >= 0 ] (?, 2) f9(a, b) -> f9(a + 1, c) [ 5 >= a /\ 0 >= c + 1 /\ -a + 5 >= 0 ] (?, 1) f9(a, b) -> f20(a, 0) [ 5 >= a ] (1, 1) f0(a, b) -> f9(c, b) start location: f0 leaf cost: 1 By chaining the transition f9(a, b) -> f20(a - 8, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ a - 7 >= 3 ] with all transitions in problem 16, the following new transitions are obtained: f9(a, b) -> f9(a - 8, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ a - 7 >= 3 /\ 2 >= a - 8 ] f9(a, b) -> f20(a - 9, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ a - 7 >= 3 /\ a - 8 >= 3 ] We thus obtain the following problem: 17: T: (1, 10) f9(a, b) -> f9(a - 8, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ a - 7 >= 3 /\ 2 >= a - 8 ] (1, 10) f9(a, b) -> f20(a - 9, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ a - 7 >= 3 /\ a - 8 >= 3 ] (1, 9) f9(a, b) -> f9(a - 7, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ 2 >= a - 7 ] (1, 8) f9(a, b) -> f9(a - 6, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ 2 >= a - 6 ] (1, 7) f9(a, b) -> f9(a - 5, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ 2 >= a - 5 ] (?, 6) f9(a, b) -> f9(a - 4, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ 2 >= a - 4 ] (?, 1) f20(a, b) -> f9(a, b) [ 2 >= a ] (?, 1) f20(a, b) -> f20(a - 1, b) [ a >= 3 ] (?, 2) f9(a, b) -> f9(a + 1, c) [ 5 >= a /\ c >= 1 /\ -a + 5 >= 0 ] (?, 2) f9(a, b) -> f9(a + 1, c) [ 5 >= a /\ 0 >= c + 1 /\ -a + 5 >= 0 ] (?, 1) f9(a, b) -> f20(a, 0) [ 5 >= a ] (1, 1) f0(a, b) -> f9(c, b) start location: f0 leaf cost: 1 By chaining the transition f9(a, b) -> f20(a - 9, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ a - 7 >= 3 /\ a - 8 >= 3 ] with all transitions in problem 17, the following new transitions are obtained: f9(a, b) -> f9(a - 9, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ a - 7 >= 3 /\ a - 8 >= 3 /\ 2 >= a - 9 ] f9(a, b) -> f20(a - 10, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ a - 7 >= 3 /\ a - 8 >= 3 /\ a - 9 >= 3 ] We thus obtain the following problem: 18: T: (1, 11) f9(a, b) -> f9(a - 9, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ a - 7 >= 3 /\ a - 8 >= 3 /\ 2 >= a - 9 ] (1, 11) f9(a, b) -> f20(a - 10, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ a - 7 >= 3 /\ a - 8 >= 3 /\ a - 9 >= 3 ] (1, 10) f9(a, b) -> f9(a - 8, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ a - 7 >= 3 /\ 2 >= a - 8 ] (1, 9) f9(a, b) -> f9(a - 7, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ 2 >= a - 7 ] (1, 8) f9(a, b) -> f9(a - 6, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ 2 >= a - 6 ] (1, 7) f9(a, b) -> f9(a - 5, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ 2 >= a - 5 ] (?, 6) f9(a, b) -> f9(a - 4, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ 2 >= a - 4 ] (?, 1) f20(a, b) -> f9(a, b) [ 2 >= a ] (?, 1) f20(a, b) -> f20(a - 1, b) [ a >= 3 ] (?, 2) f9(a, b) -> f9(a + 1, c) [ 5 >= a /\ c >= 1 /\ -a + 5 >= 0 ] (?, 2) f9(a, b) -> f9(a + 1, c) [ 5 >= a /\ 0 >= c + 1 /\ -a + 5 >= 0 ] (?, 1) f9(a, b) -> f20(a, 0) [ 5 >= a ] (1, 1) f0(a, b) -> f9(c, b) start location: f0 leaf cost: 1 By chaining the transition f9(a, b) -> f20(a - 10, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ a - 7 >= 3 /\ a - 8 >= 3 /\ a - 9 >= 3 ] with all transitions in problem 18, the following new transitions are obtained: f9(a, b) -> f9(a - 10, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ a - 7 >= 3 /\ a - 8 >= 3 /\ a - 9 >= 3 /\ 2 >= a - 10 ] f9(a, b) -> f20(a - 11, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ a - 7 >= 3 /\ a - 8 >= 3 /\ a - 9 >= 3 /\ a - 10 >= 3 ] We thus obtain the following problem: 19: T: (1, 12) f9(a, b) -> f9(a - 10, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ a - 7 >= 3 /\ a - 8 >= 3 /\ a - 9 >= 3 /\ 2 >= a - 10 ] (1, 12) f9(a, b) -> f20(a - 11, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ a - 7 >= 3 /\ a - 8 >= 3 /\ a - 9 >= 3 /\ a - 10 >= 3 ] (1, 11) f9(a, b) -> f9(a - 9, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ a - 7 >= 3 /\ a - 8 >= 3 /\ 2 >= a - 9 ] (1, 10) f9(a, b) -> f9(a - 8, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ a - 7 >= 3 /\ 2 >= a - 8 ] (1, 9) f9(a, b) -> f9(a - 7, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ 2 >= a - 7 ] (1, 8) f9(a, b) -> f9(a - 6, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ 2 >= a - 6 ] (1, 7) f9(a, b) -> f9(a - 5, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ 2 >= a - 5 ] (?, 6) f9(a, b) -> f9(a - 4, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ 2 >= a - 4 ] (?, 1) f20(a, b) -> f9(a, b) [ 2 >= a ] (?, 1) f20(a, b) -> f20(a - 1, b) [ a >= 3 ] (?, 2) f9(a, b) -> f9(a + 1, c) [ 5 >= a /\ c >= 1 /\ -a + 5 >= 0 ] (?, 2) f9(a, b) -> f9(a + 1, c) [ 5 >= a /\ 0 >= c + 1 /\ -a + 5 >= 0 ] (?, 1) f9(a, b) -> f20(a, 0) [ 5 >= a ] (1, 1) f0(a, b) -> f9(c, b) start location: f0 leaf cost: 1 By chaining the transition f9(a, b) -> f20(a - 11, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ a - 7 >= 3 /\ a - 8 >= 3 /\ a - 9 >= 3 /\ a - 10 >= 3 ] with all transitions in problem 19, the following new transitions are obtained: f9(a, b) -> f9(a - 11, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ a - 7 >= 3 /\ a - 8 >= 3 /\ a - 9 >= 3 /\ a - 10 >= 3 /\ 2 >= a - 11 ] f9(a, b) -> f20(a - 12, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ a - 7 >= 3 /\ a - 8 >= 3 /\ a - 9 >= 3 /\ a - 10 >= 3 /\ a - 11 >= 3 ] We thus obtain the following problem: 20: T: (1, 13) f9(a, b) -> f9(a - 11, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ a - 7 >= 3 /\ a - 8 >= 3 /\ a - 9 >= 3 /\ a - 10 >= 3 /\ 2 >= a - 11 ] (1, 13) f9(a, b) -> f20(a - 12, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ a - 7 >= 3 /\ a - 8 >= 3 /\ a - 9 >= 3 /\ a - 10 >= 3 /\ a - 11 >= 3 ] (1, 12) f9(a, b) -> f9(a - 10, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ a - 7 >= 3 /\ a - 8 >= 3 /\ a - 9 >= 3 /\ 2 >= a - 10 ] (1, 11) f9(a, b) -> f9(a - 9, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ a - 7 >= 3 /\ a - 8 >= 3 /\ 2 >= a - 9 ] (1, 10) f9(a, b) -> f9(a - 8, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ a - 7 >= 3 /\ 2 >= a - 8 ] (1, 9) f9(a, b) -> f9(a - 7, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ 2 >= a - 7 ] (1, 8) f9(a, b) -> f9(a - 6, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ 2 >= a - 6 ] (1, 7) f9(a, b) -> f9(a - 5, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ 2 >= a - 5 ] (?, 6) f9(a, b) -> f9(a - 4, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ 2 >= a - 4 ] (?, 1) f20(a, b) -> f9(a, b) [ 2 >= a ] (?, 1) f20(a, b) -> f20(a - 1, b) [ a >= 3 ] (?, 2) f9(a, b) -> f9(a + 1, c) [ 5 >= a /\ c >= 1 /\ -a + 5 >= 0 ] (?, 2) f9(a, b) -> f9(a + 1, c) [ 5 >= a /\ 0 >= c + 1 /\ -a + 5 >= 0 ] (?, 1) f9(a, b) -> f20(a, 0) [ 5 >= a ] (1, 1) f0(a, b) -> f9(c, b) start location: f0 leaf cost: 1 By chaining the transition f9(a, b) -> f20(a - 12, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ a - 7 >= 3 /\ a - 8 >= 3 /\ a - 9 >= 3 /\ a - 10 >= 3 /\ a - 11 >= 3 ] with all transitions in problem 20, the following new transitions are obtained: f9(a, b) -> f9(a - 12, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ a - 7 >= 3 /\ a - 8 >= 3 /\ a - 9 >= 3 /\ a - 10 >= 3 /\ a - 11 >= 3 /\ 2 >= a - 12 ] f9(a, b) -> f20(a - 13, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ a - 7 >= 3 /\ a - 8 >= 3 /\ a - 9 >= 3 /\ a - 10 >= 3 /\ a - 11 >= 3 /\ a - 12 >= 3 ] We thus obtain the following problem: 21: T: (1, 14) f9(a, b) -> f9(a - 12, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ a - 7 >= 3 /\ a - 8 >= 3 /\ a - 9 >= 3 /\ a - 10 >= 3 /\ a - 11 >= 3 /\ 2 >= a - 12 ] (1, 14) f9(a, b) -> f20(a - 13, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ a - 7 >= 3 /\ a - 8 >= 3 /\ a - 9 >= 3 /\ a - 10 >= 3 /\ a - 11 >= 3 /\ a - 12 >= 3 ] (1, 13) f9(a, b) -> f9(a - 11, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ a - 7 >= 3 /\ a - 8 >= 3 /\ a - 9 >= 3 /\ a - 10 >= 3 /\ 2 >= a - 11 ] (1, 12) f9(a, b) -> f9(a - 10, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ a - 7 >= 3 /\ a - 8 >= 3 /\ a - 9 >= 3 /\ 2 >= a - 10 ] (1, 11) f9(a, b) -> f9(a - 9, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ a - 7 >= 3 /\ a - 8 >= 3 /\ 2 >= a - 9 ] (1, 10) f9(a, b) -> f9(a - 8, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ a - 7 >= 3 /\ 2 >= a - 8 ] (1, 9) f9(a, b) -> f9(a - 7, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ a - 6 >= 3 /\ 2 >= a - 7 ] (1, 8) f9(a, b) -> f9(a - 6, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ a - 5 >= 3 /\ 2 >= a - 6 ] (1, 7) f9(a, b) -> f9(a - 5, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ a - 4 >= 3 /\ 2 >= a - 5 ] (?, 6) f9(a, b) -> f9(a - 4, b) [ a >= 6 /\ a >= 3 /\ a - 1 >= 3 /\ a - 2 >= 3 /\ a - 3 >= 3 /\ 2 >= a - 4 ] (?, 1) f20(a, b) -> f9(a, b) [ 2 >= a ] (?, 1) f20(a, b) -> f20(a - 1, b) [ a >= 3 ] (?, 2) f9(a, b) -> f9(a + 1, c) [ 5 >= a /\ c >= 1 /\ -a + 5 >= 0 ] (?, 2) f9(a, b) -> f9(a + 1, c) [ 5 >= a /\ 0 >= c + 1 /\ -a + 5 >= 0 ] (?, 1) f9(a, b) -> f20(a, 0) [ 5 >= a ] (1, 1) f0(a, b) -> f9(c, b) start location: f0 leaf cost: 1 Complexity upper bound ? Time: 3.381 sec (SMT: 3.187 sec)